2010
DOI: 10.2174/1876537801002010019
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of the Superconductor LaCaBaCu3O7~!2010-02-11~!2010-04-01~!2010-06-29~!

Abstract: LaCaBaCu 3 O 7 (La1113) is a superconductor below T C(onset) =80K and its structure is similar to the tetragonal YBCO. In this work the magnetic properties of a bulk La1113 sample are reported and compared to those of YBCO superconductor. We explore a possibly relation of this property to its particular crystalline structure, particularly to the oxygen deficiency. In contrast to a bulk YBCO, some magnetic characteristics of La1113 below T C are: the magnetic flux can penetrate easily the bulk in its vortex reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…31) However in contrast to YBCO which at 77 K can support external magnetic fields up to 6 Â 10 4 Oe (or even more depending on its purity), 32) the La1113 can support less than 1 Â 10 4 Oe under the same conditions without losing its superconductivity. 33) This apparent ''disadvantage'' of La1113 could be useful for the fabrication of superconducting transistors controlled by relatively low applied magnetic fields as a transistor gate. Figure 5 shows a design of an external magnetic field gated superconducting transistor, in which, with the help of alkane (di)thiols, a superconductor nanograin bridges two gold (or other metal) electrodes, the source (S) and the drain (D).…”
Section: Resultsmentioning
confidence: 99%
“…31) However in contrast to YBCO which at 77 K can support external magnetic fields up to 6 Â 10 4 Oe (or even more depending on its purity), 32) the La1113 can support less than 1 Â 10 4 Oe under the same conditions without losing its superconductivity. 33) This apparent ''disadvantage'' of La1113 could be useful for the fabrication of superconducting transistors controlled by relatively low applied magnetic fields as a transistor gate. Figure 5 shows a design of an external magnetic field gated superconducting transistor, in which, with the help of alkane (di)thiols, a superconductor nanograin bridges two gold (or other metal) electrodes, the source (S) and the drain (D).…”
Section: Resultsmentioning
confidence: 99%
“…whereas, at x=0.5 the composition is losing its superconductivity. It is known that a small changes in the crystalline structure of a high temperature cuprate superconductor (HTCS) produce large changes in its magnetic properties [31]. The structural changes are produced by chemical substitutions of cations or anions.…”
Section: Resistivity Properties Of La X Y 1-x Ba 2 Cu 3 O 7-δmentioning
confidence: 99%
“…Thus, altering the position and occupancy of the atoms situated in the superconducting planes CuO 2 and also leads to increasing (or decreasing) the superconducting critical temperature (Tc). Indeed Luis et al [31] reported that by changing the oxygen content in the superconductor YBa 2 Cu 3 O 7 (YBCO-7) to ≤ 6.4, the occupancy of the oxygen situated in the Cu-O chains decreases and the crystalline structure changes from orthorhombic to tetragonal where the superconductivity is destroyed. transition at Tc = 95 K. A slightly higher Tc= 96 K for the x=0.4 sample behavior followed by a superconducting transition at x=0.6, Tc= 83 K [26,32].…”
Section: Resistivity Properties Of La X Y 1-x Ba 2 Cu 3 O 7-δmentioning
confidence: 99%
“…Los resultados obtenidos en este periodo de investigación son publicados en la Revista de Investigación de Física de la UNMSM [44], en la Revista Peruana de Química e Ing. Química de la UNMSM [45][46][47], en la revista de la Sociedad Química del Perú [9,14,[48][49][50], en el Advances in Science and Technology [16], en el Journal of Physics and Chemistry of Solids [51,52], en el Open Journal of Superconductivity [53], en el Japanese Journal of Applied Physics [39] y en el Hyperfine Interactions [54] La investigación de materiales superconductores es una disciplina que requiere de proyectos financiados para poder solventar no sólo la compra de los materiales precursores sino las medidas de caracterización en costosos equipos y para el acceso a la información de trabajos de otros investigadores. Por citar un par de ejemplos, una medida de la susceptibilidad magnética de una muestra de 100 mg en el rango de temperatura de 5 a 100 K usando un magnetómetro con sensor SQUID cuesta aproximadamente 300 Nuevos Soles, 75 euros; el acceso a la literatura científica, significa un costo elevado, medio millón de dólares americanos por año en suscripciones a revistas de investigación.…”
Section: Período 2006 -2011unclassified